2008
DOI: 10.1159/000121324
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Biodegradation of Aromatic Hydrocarbons: Pathways and Prospects

Abstract: Aromatic hydrocarbons contaminate many environments worldwide, and their removal often relies on microbial bioremediation. Whereas aerobic biodegradation has been well studied for decades, anaerobic hydrocarbon biodegradation is a nascent field undergoing rapid shifts in concept and scope. This review presents known metabolic pathways used by microbes to degrade aromatic hydrocarbons using various terminal electron acceptors; an outline of the few catabolic genes and enzymes currently characterized; and specul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
162
0
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(184 citation statements)
references
References 365 publications
(257 reference statements)
2
162
0
20
Order By: Relevance
“…The stability and persistence of diverse microorganisms in methanogenic hydrocarbondegrading environments after long-term incubation suggests that these organisms are important for syntrophic growth of the communities. Figure 2a shows the pathways and genes/enzymes known to be involved in the anaerobic metabolism of various hydrocarbons (for example, reviewed by Foght, 2008;Callaghan, 2013). Characterized hydrocarbon activation mechanisms (Figure 2) include addition to fumarate (pathways 1, 2, 3, 5 and 7), hydroxylation (pathway 1) and carboxylation (pathways 4 and 6).…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingmentioning
confidence: 99%
“…The stability and persistence of diverse microorganisms in methanogenic hydrocarbondegrading environments after long-term incubation suggests that these organisms are important for syntrophic growth of the communities. Figure 2a shows the pathways and genes/enzymes known to be involved in the anaerobic metabolism of various hydrocarbons (for example, reviewed by Foght, 2008;Callaghan, 2013). Characterized hydrocarbon activation mechanisms (Figure 2) include addition to fumarate (pathways 1, 2, 3, 5 and 7), hydroxylation (pathway 1) and carboxylation (pathways 4 and 6).…”
Section: Community Compositions Of Methanogenic Hydrocarbon-degradingmentioning
confidence: 99%
“…The capacity of microorganisms to degrade a broad range of n-alkanes and crude oils under methanogenic conditions has been repeatedly reported (Anderson & Lovley, 2000;Embree et al, 2014;Foght, 2008;Gieg et al, 2008;Gray et al, 2011;Siddique et al, 2006Siddique et al, , 2011Townsend et al, 2003;Zengler et al, 1999), and the underlying mechanisms have been the subject of intense investigation. The requisite metabolic routes minimally involve syntrophic associations between bacteria capable of n-alkane activation and methanogenic archaea that consume acetate and/or hydrogen produced during the course of hydrocarbon decay.…”
mentioning
confidence: 96%
“…Benzene was the least preferred by benzoate enriched degraders. The energy requirements for the degradation of BTEX compounds are in the following order: xylenes < ethylbenzene < toluene < benzene (Foght, 2008). Although bacterial strains that could degrade individual BTEX compounds were found to grow on benzoate, necessary enzymes and the intermediates were typically not found during their growth on benzoate (Rabus and Heider, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Nales et al (1998) also observed that the presence of TEX inhibited the anaerobic benzene degradation in microcosms. This preferential degradation could be due to the less energy requirements for activation of TEX degradation than for activation of benzene degradation (Foght, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation